WRITING STRATEGY and FACTORS CONTRIBUTING to EFL UNIVERSITY STUDENTSâ€™ PREFERENCE - atik umamah; Ika - hidayanti (IAIN Syekh Nurjati Cirebon, 2018)
This study was aimed to identify 1) the significant difference on the learning strategy attainment by male and female students, 2) the significant difference on the use of the strategies in learning writing based on the studentsâ€™ attitude toward English writing â€œlike or dislikeâ€, and 3) the correlation between learning strategy use and three factors: gender, interest and writing achievement. To elicit research data, a-70 item questionnire was administered to101 English students of Universitas Islam Malang. Ex-post facto and correlation analysis were designs adopted to deal with the problems proposed in this research. The statistical analysis indicated that female students did not deploy the strategies significantly different from the male counterparts. The second finding revealed that the more interested the students in English writing, the more likely they employed the learning strategies. The last report showed that there was no correlation between writing strategy and two factors: gender and writing achievement. Meanwhile, negative-moderate correlation was found between the strategy choice and the studentsâ€™ liking for English writing. Â Â Â